A Critical Study of the Wage System and Practice in Indonesia From the Maqashid al-Shariah - Nur Mardhiah (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2022)
This study aims to analyze the wage system and practice in Indonesia from the perspective of Maqashid al-Shariah. The indicators can be seen from several applicable policies, whether they have brought benefits to the workers/laborers or not. This can be answered with an in-depth study and study seen from several aspects, including; list of decent living needs (KHL), specialization and division of labor as the basis for setting wages, wage transparency, and human resource development within companies in Indonesia. As for the methods and techniques of analysis using the content of data analysis carried out qualitatively by making interpretations of policies, rules, and empirical data obtained, then concluded as answers to research problems. Findings in the field reveal that from systems and policies, as well as practices, some companies are still unable to provide decent wages to workers/laborers or even do not meet decent living standards (KHL) in Indonesia. In addition, there are policies and regulations that come from the government or companies that are not in line due to internal factors of the company itself. This research is here to try to provide an affirmative solution by integrating the indicators of the benefit of the Maqashid al-Shariah on improving the policy and wage system in Indonesia